Pengaruh Bahan Ajar Fisika Berbasis Inkuiri untuk Meningkatkan Kemampuan Berpikir Kreatif Peserta Didik pada Materi Momentum, Impuls dan Getaran Harmonik Sederhana Kelas X SMAN 8 Padang - Naimis Syifa Hasibuan; Hufri Hufri (Universitas Negeri Padang, 2018)
The 2013 curriculum aims to encourage students to be more active in the learning process. The fact in the school shows that 2013 curriculum has not been fully implemented and there are still limited module that can improve students' creative thinking. One of the solution is to use inquiry-based module in learning. This study aims to search the effect of the use of inquiry-based physics module learning on subject of momentum, impulse and harmonic vibration to enhance the students’ creative thinking in X SMAN 8 Padang. Research conducted included the type of Quasi Experiment Research. The population of this study were all students of class X of SMAN 8 Padang at 2017/2018 period. Sampling technique was carried out by purposive sampling technique. Research data is the learning outcomes of students’ creative thinking. The research instrument is the final test to measure the students’ creative thingking. The research data was analyzed with two average similarity tests. Based on data analysis that has been done after using inquiry-based physics module, two research results have been obtained. First, the average value of students’ creative thinking in both sample classes was 79.84 and 76.36. From the Man Withney test, p<α is obtained, so the alternative hypothesis is accepted. Second, the results of the normalized gain test in the experimental class obtained g> 0.70, so that the students’ creative thinking in all four aspects experienced a high increase.